2017
DOI: 10.3153/jfhs17019
|View full text |Cite
|
Sign up to set email alerts
|

Some Bioactive Properties of Wild and Commercial Mushroom Species

Abstract: Abstract:In this study, the protein and total phenolic contents of some commercially cultivated (Agaricus bisporus, Pleurotus ostreatus) and wild mushrooms (Amanita caesarea, Fistulina hepatica, Meripilus giganteus) were determined. Antioxidant and antimicrobial properties of these mushrooms against Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae, Salmonella typhimurium, Acinetobacter haemolyticus, Proteus mirabilis, Pseudomonas aeruginosa and Candida albicans were also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been found that mushrooms also have various pharmacological properties in addition to their nutritional value. Previous studies have reported that mushrooms had antioxidant, antimicrobial, anticancer, antiproliferative, DNA-protective, antiallergic, analgesic, antitumor, immunosuppressive, antiatherogenic, hypoglycemic, anti-inflammatory, hepatoprotective activities (Yang et al 2008, Hetland et al 2011, Patel and Goyal 2012, Ren et al 2012, Li et al 2013, Soares et al 2013, Sun et al 2014, Elsayed et al 2014, Yıldız et al 2015, Bal et al 2017, Béni et al 2018. Also, it has been found that Lycoperdon sp.…”
Section: Introductionmentioning
confidence: 97%
“…It has been found that mushrooms also have various pharmacological properties in addition to their nutritional value. Previous studies have reported that mushrooms had antioxidant, antimicrobial, anticancer, antiproliferative, DNA-protective, antiallergic, analgesic, antitumor, immunosuppressive, antiatherogenic, hypoglycemic, anti-inflammatory, hepatoprotective activities (Yang et al 2008, Hetland et al 2011, Patel and Goyal 2012, Ren et al 2012, Li et al 2013, Soares et al 2013, Sun et al 2014, Elsayed et al 2014, Yıldız et al 2015, Bal et al 2017, Béni et al 2018. Also, it has been found that Lycoperdon sp.…”
Section: Introductionmentioning
confidence: 97%
“…Mushrooms are not only consumed as nutritional foods but also have antimicrobial, antioxidant, anti-proliferative, anti-aging, anticancer, apoptotic and DNA-protective effects (7,8). These properties are thanks to their bioactive molecules, and accordingly, those molecules are studied in the contents of mushroom composites (9).…”
Section: Introductionmentioning
confidence: 99%